KEY DETERMINANTS OF GOVERNMENT AUDITOR’S BEHAVIOUR TO ADOPT BIG DATA ANALYTICS IN AUDIT PRACTICE - Jiwandono, Ahmad Ikhlasul; Sofyani, Hafiez (Universitas Bunda Mulia, 2024)
Background: Despite the increasing adoption of big data and Big Data Analytics (BDA) in the business world, the accounting and audit profession is considered slow in taking advantage of these innovative developments. Government auditors play an important role indirectly in improving good governance. The use of BDA in government audits has been carried out in Indonesia since 2020. However, because its use is not mandatory, not all government auditors use the application.Objective: This research investigates the key determinants that drive government auditors' behaviour to adopt BDA technology in audit practice, especially in the Indonesian context, with a focus on the Indonesian Supreme Audit Agency (SAA).Research Method: This study was conducted through a questionnaire survey involving 126 government auditors in Indonesia. Meanwhile, research data was analyzed using the Structural Equation Modelling - Partial Least Square method (SEM-PLS).Research Results: Research findings show that performance expectancy and effort expectancy have a direct influence on auditors' intentions to use BDA techniques at SAA. Meanwhile, the auditor's intention to use BDA techniques has a significant effect on Actual Use.Originality/Novelty of Research: This research addresses the gap about factors that encourage auditors' behaviour to adopt BDA technology in audit practice, especially in public sector context.